2019
DOI: 10.1002/ece3.5358
|View full text |Cite
|
Sign up to set email alerts
|

Development of sexual dimorphism in two sympatric skinks with different growth rates

Abstract: Sexual size dimorphism (SSD) is widespread in animals, especially in lizards (Reptilia: Squamata), and is driven by fecundity selection, male–male competition, or other adaptive hypotheses. However, these selective pressures may vary through different life history periods; thus, it is essential to assess the relationship between growth and SSD. In this study, we tracked SSD dynamics between a “fading‐tail color skink” (blue tail skink whose tail is only blue during its juvenile stage: Plestiodon el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(61 reference statements)
0
6
0
2
Order By: Relevance
“…While active, they are constantly on the move in search of food, and many aspects of their ecology, such as habitat use, types of prey they consume, and predators and anti‐predatory strategies, are expected to differ markedly from those of adults (Morafka et al, 2000; Vitt, 2000). In particular, in many Plestiodon species, including P. lynxe , the tail of neonates or hatchlings is bright blue, while this colour is lost or less conspicuous in adults (Hawlena et al, 2006; Yang et al, 2019) and, at least in some species, this difference in colour has been shown to imply a difference in their anti‐predatory strategies (Cooper Jr. & Vitt, 1985; Vitt & Cooper Jr., 1986b). In neonates, which are constantly on the move, the striking blue colour deflects predatory attacks towards the tail, while adults, who tend to be more sedentary, often rely on camouflage to avoid predation.…”
Section: Discussionmentioning
confidence: 99%
“…While active, they are constantly on the move in search of food, and many aspects of their ecology, such as habitat use, types of prey they consume, and predators and anti‐predatory strategies, are expected to differ markedly from those of adults (Morafka et al, 2000; Vitt, 2000). In particular, in many Plestiodon species, including P. lynxe , the tail of neonates or hatchlings is bright blue, while this colour is lost or less conspicuous in adults (Hawlena et al, 2006; Yang et al, 2019) and, at least in some species, this difference in colour has been shown to imply a difference in their anti‐predatory strategies (Cooper Jr. & Vitt, 1985; Vitt & Cooper Jr., 1986b). In neonates, which are constantly on the move, the striking blue colour deflects predatory attacks towards the tail, while adults, who tend to be more sedentary, often rely on camouflage to avoid predation.…”
Section: Discussionmentioning
confidence: 99%
“…Esta tendencia también ocurre en Plestiodon. En la mayoría de las especies de escíncidos de cola azul estudiadas hasta la fecha un sexo es más grande que el otro (Breckenridge, 1943;Vitt y Cooper, 1985;Vitt y Coper, 1986;Huang, 1996;Du y Ji, 2001;Hikida et al, 2001;Yang et al, 2019) y hasta donde sabemos solo se conocen dos especies de Plestiodon monomórficas con respecto al tamaño corporal, P. fasciatus (Vitt y Cooper, 1986) y P. sp (el presente estudio).…”
Section: Dimorfismo Sexual En Tamaño Corporalunclassified
“…En las especies estadounidenses P. septentrionalis, P. inexpectatus y P. laticeps los machos son más grandes que las hembras, si bien P. fasciatus es monomórfica en este aspecto (Breckenridge, 1943;Vitt y Cooper, 1985;Vitt y Cooper, 1986). Asimismo, se ha encontrado DST, con machos más grandes que las hembras, en las especies asiáticas P. chinensis, P. quadrilineatus, P. elegans, P. latiscustatus y P. tamdaoensis (Lin y Ji, 2000;Huang, 1996;Du y Ji, 2001;Hikida et al, 2001;Yang et al, 2019). En todas las especies estadounidenses y asiáticas señaladas anteriormente los machos tienen cabezas más grandes que las hembras y en la mayoría de ellas se han registrado combates y encuentros agresivos entre los machos, lo que ha conducido a asumir que el dimorfismo sexual en el tamaño de la cabeza es consecuencia de la selección sexual (Vitt y Cooper, 1985;Vitt y Cooper, 1986;Huang, 1996;Du y Ji, 2001).…”
Section: Introductionunclassified
“…These factors vary and are uncontrolled in the wild, and may influence ontogenetic color changes. Third, obvious differences exist in the growth rules between the sexes of skink (Yang et al, 2019 ); however, it is unclear how the tails of different sexes vary in terms of ontogenetic color change.…”
Section: Introductionmentioning
confidence: 99%
“…These factors vary and are uncontrolled in the wild, and may influence ontogenetic color changes. Third, obvious differences exist in the growth rules between the sexes of skink (Yang et al, 2019); however, it is unclear how the tails of different sexes vary in terms of ontogenetic color change. Therefore, we selected the small fade-tail skink (blue-tailed skink: Plestiodon elegans) to analyze the slow color change in its tail in the laboratory.…”
mentioning
confidence: 99%